Sposoby przeciwstawiania się złemu duchowi w ujęciu św. Jana Chryzostoma - Adam Zmuda (Vox Patrum, 2013)
In the opinion of Saint John Chrysostom man can resist the demon through the adoption of the sacrament of Baptism and the Eucharist and through the practice of penance: prayer, fasting and almsgiving. In the Sacrament of Baptism, all works of the devil are removed, man becomes an heir of heaven, marrying the son of God takes place, the Holy Spirit begins to dwell in man. In the Eucharist, Christ together with the person who welcomed him in Holy Communion, fights with the devil, just like in the times when he walked on the earth, throws out the evil spirit, kindles the heart of the believer and gives grace to fight. After the fall, that is after the cooperation with the devil, man immediately has to take to the works of penance, to return to unity with betrayed God. Not doing works of penance equals condemning himself. One should fight by prayer – during which one asks God for strength to fight, by fasting – which extinguishes the evil passions and „moves so much evil away from us” and by almsgiving – which removes the lust, opens the gates of heaven, takes away sins.